INCREASING INFORMATION AT INTERSECTIONS WITH THE ORGANIZATION OF A SPLIT PHASE DISTRACTS - Прохорчук, Марина (SWorldJournal, 2025)
The article deals with the problems of traffic safety at intersections equipped with traffic signal control, where the time of the permitted signal on one street may have different duration on the approaches to the intersection. This method of organizing